EVOLUTION AND PROSPECTS OF JAPAN’S ASIAN POLICY (Conferencea, 2022)
Cooperation in the fields of trade, finance and security in the Asian region was carried out mainly on the basis of bilateral agreements during the post-war period. Since 2010, significant progress has been made through multilateral cooperation. As a result of the effective operation of a number of regional organizations, multilateral functions have been significantly improved. This article examines Japan’s pursuit of multilateralism in its foreign policy toward Asia as a strategy to realize the country’s interests and highlights the need for Japan to intensify its coalition-building efforts as part of its Asian policy.